An experimental study of a phase change storage system - Hawlader, Mohammad Nurul Alam; Smita, Panga (IIUM Press, 2011)
This paper describes the heat transfer process and the movement of the solid-liquid interface when the energy is added to a PCM, paraffin wax, through a vertical wall heated under conditions of uniform heat flux and constant temperature. Experiments indicate that the initial mode of heat transfer in the melting process was purely conduction controlled, and early convection due to volumetric expansion of the liquid PCM was followed by the solely buoyancy driven natural convection within the liquid. At this stage, the superheating of the liquid led to a combined convection and conduction mode of heat transfer until eventually conduction became the dominant mode of heat transfer. Superheating and subcooling of the PCM reduce the rate of propagation of the solid-liquid interface. Numerical simulation, based on the enthalpy formulation, indicated the presence of convection in the fluid region of the PCM, which is confirmed by the results from the experiments.